A Semi-Lagrangian Approach for Dilute Non-Collisional Fluid-Particle Flows (Communications in Computational Physics, 2018)
We develop numerical methods for the simulation of laden-flows where particlesinteract with the carrier fluid through drag forces. Semi-Lagrangian techniquesare presented to handle the Vlasov-type equation which governs the evolution of theparticles. We discuss several options to treat the coupling with the hydrodynamicsystem describing the fluid phase, paying attention to strategies based on staggereddiscretizations of the fluid velocity.